Correlation of LMP-1 Expression with BCL11B in Undifferentiated Type Nasopharyngeal Carcinoma - Ihda Dian Kusuma; Diah Prabawati Retnani; Hendy Setyo Yudhanto; Harun Al Rasyid; Kenty Wantri Anita (HM Publisher, 2022)
Background: Nasopharyngeal carcinoma (NPC) is an endemic malignancy in Asia and in Indonesia with a high incidence and mortality. The high mortality rate of patients with NPC is caused by recurrence and metastases early in the disease process, even though they have been given a combination of standard NPC therapy, namely radiotherapy and chemotherapy. Recurrences generally occur after the initial modalities of radiotherapy. Toxicity due to therapy given over a long time can also increase mortality. This study aims to determine the expression of BCL11B in undifferentiated NPC and its correlation with LMP-1 so that it can provide an overview of the nature of CSC in NPC, which is thought to cause recurrence and metastases and provide a poor prognosis in patients with NPC. Methods: This study was an analytical observational study using a cross-sectional approach using 30 samples from nasopharyngeal biopsy tissue diagnosed with undifferentiated NPC at the anatomical pathology installation of Dr. Saiful Anwar General Hospital, Malang, Indonesia, between 2018-2020. LMP-1 and BCL11B expression was examined using the immunohistochemical method. Data analysis was performed univariate and bivariate with the help of SPSS software. Results: Statistical analysis using the Spearman correlation test between LMP-1 and BCL11B expression in undifferentiated NPC biopsy tissue showed a significant correlation (p=0.004) with a correlation coefficient of r=-0.511. Conclusion: The higher the expression of LMP-1, the lower the expression of BCL11B in nasopharyngeal biopsies of patients with undifferentiated.